2014
DOI: 10.1371/journal.pmed.1001735
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Treatment of Malaria in Pregnancy with Mefloquine in HIV-Infected Women Receiving Cotrimoxazole Prophylaxis: A Multicenter Randomized Placebo-Controlled Trial

Abstract: Clara Menéndez and colleagues conducted a randomized controlled trial among HIV-positive pregnant women in Kenya, Mozambique, and Tanzania to investigate the safety and efficacy of mefloquine as intermittent preventative therapy for malaria in women receiving cotrimoxazole prophylaxis and long-lasting insecticide treated nets. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 55 publications
2
112
0
Order By: Relevance
“…However, recent publications, which assessed MQ on LBW as primary end point and suggested a positive interaction between MQ-IPTp and MTCT in HIV-infected women, incited WHO working groups not to recommend MQ in this indication. 7,9,10 Generally, when a trial involves therapies for life-threatening conditions such as antimalarial drugs, which can potentially save newborns' lives, several outcomes should be systematically taken into account. Judging by a sole, albeit important, criterion may lead to permanently ruling out a potentially important drug, given its high efficacy and the heavy burden of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent publications, which assessed MQ on LBW as primary end point and suggested a positive interaction between MQ-IPTp and MTCT in HIV-infected women, incited WHO working groups not to recommend MQ in this indication. 7,9,10 Generally, when a trial involves therapies for life-threatening conditions such as antimalarial drugs, which can potentially save newborns' lives, several outcomes should be systematically taken into account. Judging by a sole, albeit important, criterion may lead to permanently ruling out a potentially important drug, given its high efficacy and the heavy burden of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Although concerns have been raised about a possible increase in stillbirths in women treated with curative doses of MQ, 19 this finding was confirmed neither in larger datasets nor in two recent multicenter trials on MQ for IPTp conducted in around 6,000 pregnant women. 6,7,9,20,21 As guidelines, we would recommend not including overcoming AE criteria such as stillbirths, congenital malformations, or mother-to-child transmission (MTCT) of HIV-when relevant-in the multiple outcome analysis since these outcomes have to be evaluated separately, prior to other criteria. In such cases where the drug "under test" has been associated with a significant increased risk for one of these major outcomes, we consider that the multiple outcome approach is not appropriate because the drug should not be given in this indication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Another study found that while SP should not be coadministered with CTX due to increased toxicity, women receiving CTX may still benefit from additional antimalarial prophylaxis. 26 Women receiving CTX should not be given SP; therefore, more research is needed to determine how CTX may factor into our findings and how other antimalarial drugs compare, particularly as CTX has also been associated with malaria and LBW.…”
Section: Discussionmentioning
confidence: 99%
“…The contemporaneous HIV seroprevalence among pregnant women attending the ANC clinics was 30% [15]. A prevalence of 9% of MTCT at first month of age and of 25% at the end of the first year of life has also been reported in the area [19,20]. Before 2013, PMTCT relied on antiretroviral prophylaxis, which consisted in antepartum monotherapy with zidovudine (ZDV), a singledose nevirapine (NVP) at the onset of labor, and ZDV þ lamivudine (3TC) at delivery and for 7 days post partum.…”
Section: Study Area and Populationmentioning
confidence: 99%